The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s11596-010-0559-5
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of mood stabilizers for Alzheimer’s disease

Abstract: The objective of this study was to assess the clinical evidence for or against mood stabilizers as a treatment for Alzheimer's disease (AD). We searched 5 databases from their inception to January 2010. Five randomized clinical trials of mood stabilizers to treat human patients suffering from AD were included. These trials assessed the effectiveness of mood stabilizers as an adjunct treatment to conventional anti-dementia drugs on behavioral and psychological symptoms, especially on agitation. Methodological q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…These findings are compatible with a study presenting that lysosomal acidification is malfunctioning in the PS1 knockout principal neurons and fibroblasts in Alzheimer's patients with PS1 mutations (Wolfe et al, 2013). Phase II (Forlenza et al, 2012Nicotinamide Between 1935and 1937 Improvement of autophagy-lysosome processing Phase I (D. Liu, Pitta, et al, 2013 Carbamazepine 1953 Antiepileptic Decrease mTOR activity Xiao, Su, Cao, Sun, and Liang (2010) BECN1 mimetics Autophagy regulator Initiation of autophagy and autophagosome clearance ) Haque, et al, 2016Uddin, Mamun, Takeda, Sarwar, & Begum, 2018). For successful treatment, degradation of toxic molecules is necessary.…”
Section: Ps Dysfunction and Autophagic-lysosomal System In Adsupporting
confidence: 81%
“…These findings are compatible with a study presenting that lysosomal acidification is malfunctioning in the PS1 knockout principal neurons and fibroblasts in Alzheimer's patients with PS1 mutations (Wolfe et al, 2013). Phase II (Forlenza et al, 2012Nicotinamide Between 1935and 1937 Improvement of autophagy-lysosome processing Phase I (D. Liu, Pitta, et al, 2013 Carbamazepine 1953 Antiepileptic Decrease mTOR activity Xiao, Su, Cao, Sun, and Liang (2010) BECN1 mimetics Autophagy regulator Initiation of autophagy and autophagosome clearance ) Haque, et al, 2016Uddin, Mamun, Takeda, Sarwar, & Begum, 2018). For successful treatment, degradation of toxic molecules is necessary.…”
Section: Ps Dysfunction and Autophagic-lysosomal System In Adsupporting
confidence: 81%
“…Carbamazepine was primarily developed as a drug used in the treatment of epilepsy ( Okuma and Kishimoto, 1998 ). In the past, scientists studied therapeutic effect of CBZ on AD-related agitation ( Xiao et al, 2010 ). Recently two publications have shown that carbamazepine-induced autophagy also protected against memory dysfunction and increase in Aβ content in brains of mouse model of AD ( Li et al, 2013 ; Zhang et al, 2017 ).…”
Section: Therapeutic Implications Of the Interplay Of Alzheimer’s Dismentioning
confidence: 99%
“…All of these therapeutic drugs exhibited positive effects on Aβ reduction and on alleviating AD symptoms. Nevertheless, a recent meta-analysis indicated that mood stabilizers such as CBZ and Rap were not effective but rather are harmful to AD patients [ 31 ]. More importantly, several issues in this study should be addressed by future researchers.…”
Section: Discussionmentioning
confidence: 99%